Clinical outcomes of patients with limited brain metastases treated with hypofractionated (5 × 6 Gy) conformal radiotherapy. Issue 2 (May 2017) - Lockney, Natalie A.; Wang, Diana G.; Gutin, Philip H.; Brennan, Cameron; Tabar, Viviane; Ballangrud, Ase; Pei, Xin; Chan, Timothy A.; Yamada, Yoshiya; Yang, T. Jonathan; Beal, Kathryn
Abstract: Background and purpose: Hypofractionated conformal radiotherapy (hfCRT) is used for larger brain metastases or metastases near critical structures. We investigated hfCRT outcomes for newly diagnosed brain metastases. Materials and methods: We identified 195 patients with 1–3 brain metastases who underwent 5 × 6 Gy hfCRT for 231 lesions from 2007 to 2013. Associations among clinical factors, local control (LC), distant brain control (DC) and overall survival (OS) were tested using univariate and multivariate (MVA) Cox regression analysis and Kaplan–Meier method. Results: Median follow-up was 12.8 months. One hundred forty-three (62%) lesions were treated with hfCRT post-operatively, and 88 (38%) with definitive hfCRT. LC for all lesions was 83% at 1 year. For lesions treated with post-operative hfCRT, tumor size (HR = 4.7, p  = 0.04) and subtotal resection (HR = 2.7, p  = 0.02) were predictive of local failure on MVA. For lesions ≥2.8 cm in size, LC was 61% at 12 months for lesions status-post subtotal resection, compared to 84% status-post gross total resection ( p  = 0.004). Extracranial disease presence was associated with worse DC (HR = 1.8, p  = 0.008) and OS (HR = 3.1, p  < 0.001). Conclusions: We showed 5 × 6 Gy hfCRT provides acceptable LC at 1 year for limited brain metastases. For large lesions not grossly resected, more aggressive strategies can be considered to improve LC.